2010
DOI: 10.1592/phco.30.12.1292
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Venous Thromboembolism in Patients with Human Immunodeficiency Virus Infection

Abstract: Prevention and treatment of venous thromboembolism are gaining attention in the lay and medical communities because of an increase in frequency, cost, and risk factors. Evidence shows that patients with human immunodeficiency virus (HIV) have multiple risk factors and a 2-10-fold increased risk for venous thromboembolism compared with the general population. A higher rate of venous thromboembolism also occurs in patients with HIV who are younger than 50 years (3.31% vs 0.53% in age-matched healthy controls, p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…There is an increased risk of venous thromboembolism in HIV-infected patients and several clinical studies have demonstrated this. [20] However, Horberg et al found no greater risk in HIV-infected than noninfected patients undergoing surgery in the antiretroviral therapy era. [16] In their study of 332 pairs of HIV-infected and -noninfected patients they found no excess of "cardiopulmonary" events in the HIV-infected group.…”
Section: Discussionmentioning
confidence: 98%
“…There is an increased risk of venous thromboembolism in HIV-infected patients and several clinical studies have demonstrated this. [20] However, Horberg et al found no greater risk in HIV-infected than noninfected patients undergoing surgery in the antiretroviral therapy era. [16] In their study of 332 pairs of HIV-infected and -noninfected patients they found no excess of "cardiopulmonary" events in the HIV-infected group.…”
Section: Discussionmentioning
confidence: 98%
“…Also, other study by Kiser et al [24], showed patients with HIV had higher rate of VTE, being younger than 50 years (3.31% vs 0.53% in age-matched healthy controls, p < 0.0001), had a CD4(+) cell count less than 200 cells/mm³, or a diagnosis of acquired immunodeficiency syndrome.…”
Section: Therapymentioning
confidence: 86%
“…The pathogenesis of thrombotic complications in HIV infected patients and patients with AIDS is multifactorial, with the aPL playing a role in selected patients only [5,7]. Lipid disturbances consequent on antiretroviral treatment in AIDS may be prime causes of these complications.…”
Section: Case Reportmentioning
confidence: 99%